Las formas de afrontamiento de la familia ante la enfermedad crónica de niños, niñas y adolescentes - Rosero Rivera, Eugenia (2015)
The country acceding to the Millennium Development Goals, agreed to include indicators that are specific to the health sector, the Law of the National Health System, within the policy guidelines and as a state responsibility to ensure protection of the health of the entire population. The above percentages may be related to the current population is 14,264,579 Ecuadorians; considered that the percentages regarding poverty remain, speaks of a representative group of people it requires improving the quality of life and health. Moreover, the network of hospitals and health centers in the state have large numbers of users and in many cases fail to meet demand, despite the efforts of the National Health Policy has been supporting the development of capabilities Health sector.